FUTURE PHILOLOGISTS’ COMMUNICATIVE COMPETENCE: ESSENCE OF THE CONCEPT, CONTENT, STRUCTURE - Арістова, Наталія Олександрівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
In the article different approaches to comprehend the content, structure and essence of the concept “communicative competence» are given. The essence of the concepts “competence», “key competences», “object competences», “communicative skills» are specified. The author defines the content, structure and essence of the concept “future philologists’ communicative competence». The structure of communicative competence which consists of four components is theoretically substantiated. The emphasis is made on motivational and value-based, cognitive, processual, resultative and reflective components.